Low-lying Gamow-Teller transitions in spherical nuclei - Çakmak, N.; Ünlü S.; Selam C. (My University, 2012)
The Pyatov Method has been used to study the low-lying Gamow-Teller transitions in the mass region of 98 ? A ? 130. The eigenvalues and eigenfunctions of the total Hamiltonian have been solved within the framework of proton-neutron quasiparticle random-phase approximation. The low-lying ? decay log(ft) values have been calculated for the nuclei under consideration. © 2012 Pleiades Publishing, Ltd.